Pengamanan Pesan Rahasia dengan Algoritma Vigenere Cipher Menggunakan PHP - Ira Murni; Atika Sari br pa; Bagus Rizki Lubis; Ali Ikhwan (Journal on Education, 2023)
A message security system to maintain the confidentiality of data information is very important. To achieve this, a security system is required to maintain the confidentiality of information. Encrypting information sent for cryptographic purposes confidentiality, integrity, authentication and irrefutable proof is one of the methods used for this purpose. Algorithm is a collection of problem-solving commands. Algorithm also has a process of repetition (iteration) and decisions that cannot be made. Vigenere cipher is one of the traditional cryptographic algorithms with multiple alphabetical substitution. PHP stands for PHP Hypertext Preprocessor. PHP is a scripting language that is commonly used to create dynamic web applications by deploying them on servers. The purpose of this research is to secure secret messages using the Vigenere Cipher algorithm using PHP.